Metode Penyusunan Kitab Mu'jam Al-wajiz min Ahadith Al-rasul Al-aziz - Salman Abdul Muthalib (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Mu‘jam al-Wajiz Min Ahadith al-Rasul al-‘aziz is one of classic work in  hadist, which is still written in manuscript. The manuscript is posed by Acehnese  community. It is compellation of hadist which is structured alphabetically.  Collected hadist is started by letter of alif, which is followed by ba’ and so on  following Arabic alphabet order. This structure ease people in searching particular  hadist. Moreover, the author mentioned mukharrij in every end of hadist, which is  also important to initiate takhrij hadist.